How to simplify \[\sin \left( {{{\sec }^{ - 1}}\left( x \right)} \right)\]?
Answer
Verified
439.5k+ views
Hint:
Here, we will use the Inverse Trigonometric Identity and assume the inverse trigonometric function to be some variable. We will then simplify the equation further using the trigonometric identities and basic mathematical operation to get the required answer. Trigonometric identity is an equation which is always true for all the variables.
Formula Used:
We will use the following formula:
1) Inverse Trigonometric Identity: \[{\sec ^{ - 1}}\left( x \right) = {\cos ^{ - 1}}\left( {\dfrac{1}{x}} \right)\]
2) Trigonometric Identity: \[{\sin ^2}y + {\cos ^2}y = 1\]
Complete step by step solution:
We are given a Trigonometric equation \[\sin \left( {{{\sec }^{ - 1}}\left( x \right)} \right)\].
Inverse Trigonometric Identity: \[{\sec ^{ - 1}}\left( x \right) = {\cos ^{ - 1}}\left( {\dfrac{1}{x}} \right)\] . But, this trigonometric identity is true only when \[\left| x \right| \ge 1\] since the equation is valid for values in the Domain of \[{\sec ^{ - 1}}\left( x \right)\].
Now, by using the Trigonometric Identity, we get
\[ \Rightarrow \sin \left( {{{\sec }^{ - 1}}\left( x \right)} \right) = \sin \left( {{{\cos }^{ - 1}}\left( {\dfrac{1}{x}} \right)} \right)\].
Let us consider the trigonometric function
\[y = {\cos ^{ - 1}}\left( {\dfrac{1}{x}} \right)\] ………………………………………………..\[\left( 1 \right)\]
Rewriting the equation, we get
\[ \Rightarrow \left( {\dfrac{1}{x}} \right) = \cos y\]
Squaring on both the sides, we get
\[ \Rightarrow {\left( {\dfrac{1}{x}} \right)^2} = {\cos ^2}y\]
\[ \Rightarrow \dfrac{1}{{{x^2}}} = {\cos ^2}y\]
Now we can write the identity \[{\sin ^2}y + {\cos ^2}y = 1\] as \[{\cos ^2}y = 1 - {\sin ^2}y\].
Using this trigonometric identity in above equation, we get
\[ \Rightarrow \dfrac{1}{{{x^2}}} = 1 - {\sin ^2}y\]
Rewriting the equation, we get
\[ \Rightarrow {\sin ^2}y = 1 - \dfrac{1}{{{x^2}}}\]
By taking LCM on the RHS, we get
\[ \Rightarrow {\sin ^2}y = \dfrac{{{x^2} - 1}}{{{x^2}}}\]
Taking square root on both the sides, we get
\[ \Rightarrow \sin y = \dfrac{{\sqrt {{x^2} - 1} }}{x}\]
By substituting equation \[\left( 1 \right)\] in above equation, we get
\[ \Rightarrow \sin \left( {{{\cos }^{ - 1}}\left( {\dfrac{1}{x}} \right)} \right) = \dfrac{{\sqrt {{x^2} - 1} }}{x}\]
Substituting \[{\sec ^{ - 1}}\left( x \right) = {\cos ^{ - 1}}\left( {\dfrac{1}{x}} \right)\] in the above equation, we get
\[ \Rightarrow \sin \left( {{{\sec }^{ - 1}}\left( x \right)} \right) = \dfrac{{\sqrt {{x^2} - 1} }}{x}\]
Therefore, the value of \[\sin \left( {{{\sec }^{ - 1}}\left( x \right)} \right)\]is\[\dfrac{{\sqrt {{x^2} - 1} }}{x}\].
Note:
We know that Trigonometric Equation is defined as an equation involving the trigonometric ratios. We should know that we have many trigonometric identities which are related to all the other trigonometric equations. Trigonometric Ratios of a Particular angle are the ratios of the sides of a right angled triangle with respect to any of its acute angle. Trigonometric Ratios are used to find the relationships between the sides of a right angle triangle. We should know that the inverse trigonometric function is used to find the missing angles in a right angled triangle whereas the trigonometric function is used to find the missing sides in a right angled triangle.
Here, we will use the Inverse Trigonometric Identity and assume the inverse trigonometric function to be some variable. We will then simplify the equation further using the trigonometric identities and basic mathematical operation to get the required answer. Trigonometric identity is an equation which is always true for all the variables.
Formula Used:
We will use the following formula:
1) Inverse Trigonometric Identity: \[{\sec ^{ - 1}}\left( x \right) = {\cos ^{ - 1}}\left( {\dfrac{1}{x}} \right)\]
2) Trigonometric Identity: \[{\sin ^2}y + {\cos ^2}y = 1\]
Complete step by step solution:
We are given a Trigonometric equation \[\sin \left( {{{\sec }^{ - 1}}\left( x \right)} \right)\].
Inverse Trigonometric Identity: \[{\sec ^{ - 1}}\left( x \right) = {\cos ^{ - 1}}\left( {\dfrac{1}{x}} \right)\] . But, this trigonometric identity is true only when \[\left| x \right| \ge 1\] since the equation is valid for values in the Domain of \[{\sec ^{ - 1}}\left( x \right)\].
Now, by using the Trigonometric Identity, we get
\[ \Rightarrow \sin \left( {{{\sec }^{ - 1}}\left( x \right)} \right) = \sin \left( {{{\cos }^{ - 1}}\left( {\dfrac{1}{x}} \right)} \right)\].
Let us consider the trigonometric function
\[y = {\cos ^{ - 1}}\left( {\dfrac{1}{x}} \right)\] ………………………………………………..\[\left( 1 \right)\]
Rewriting the equation, we get
\[ \Rightarrow \left( {\dfrac{1}{x}} \right) = \cos y\]
Squaring on both the sides, we get
\[ \Rightarrow {\left( {\dfrac{1}{x}} \right)^2} = {\cos ^2}y\]
\[ \Rightarrow \dfrac{1}{{{x^2}}} = {\cos ^2}y\]
Now we can write the identity \[{\sin ^2}y + {\cos ^2}y = 1\] as \[{\cos ^2}y = 1 - {\sin ^2}y\].
Using this trigonometric identity in above equation, we get
\[ \Rightarrow \dfrac{1}{{{x^2}}} = 1 - {\sin ^2}y\]
Rewriting the equation, we get
\[ \Rightarrow {\sin ^2}y = 1 - \dfrac{1}{{{x^2}}}\]
By taking LCM on the RHS, we get
\[ \Rightarrow {\sin ^2}y = \dfrac{{{x^2} - 1}}{{{x^2}}}\]
Taking square root on both the sides, we get
\[ \Rightarrow \sin y = \dfrac{{\sqrt {{x^2} - 1} }}{x}\]
By substituting equation \[\left( 1 \right)\] in above equation, we get
\[ \Rightarrow \sin \left( {{{\cos }^{ - 1}}\left( {\dfrac{1}{x}} \right)} \right) = \dfrac{{\sqrt {{x^2} - 1} }}{x}\]
Substituting \[{\sec ^{ - 1}}\left( x \right) = {\cos ^{ - 1}}\left( {\dfrac{1}{x}} \right)\] in the above equation, we get
\[ \Rightarrow \sin \left( {{{\sec }^{ - 1}}\left( x \right)} \right) = \dfrac{{\sqrt {{x^2} - 1} }}{x}\]
Therefore, the value of \[\sin \left( {{{\sec }^{ - 1}}\left( x \right)} \right)\]is\[\dfrac{{\sqrt {{x^2} - 1} }}{x}\].
Note:
We know that Trigonometric Equation is defined as an equation involving the trigonometric ratios. We should know that we have many trigonometric identities which are related to all the other trigonometric equations. Trigonometric Ratios of a Particular angle are the ratios of the sides of a right angled triangle with respect to any of its acute angle. Trigonometric Ratios are used to find the relationships between the sides of a right angle triangle. We should know that the inverse trigonometric function is used to find the missing angles in a right angled triangle whereas the trigonometric function is used to find the missing sides in a right angled triangle.
Recently Updated Pages
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Statement I Reactivity of aluminium decreases when class 11 chemistry CBSE
Trending doubts
The reservoir of dam is called Govind Sagar A Jayakwadi class 11 social science CBSE
10 examples of friction in our daily life
Difference Between Prokaryotic Cells and Eukaryotic Cells
State and prove Bernoullis theorem class 11 physics CBSE
State the laws of reflection of light
What is the chemical name of Iron class 11 chemistry CBSE